MEKANISME PENERBITAN SERTIFIKAT HAK MILIK ATAS TANAH DALAM PERJANJIAN JUAL BELI (Studi di Badan Pertanahan Nasional Kabupaten Nias Selatan) - Festina Gaho (Jurnal Panah Hukum, 2023)
The transfer of ownership rights to land is the transfer or transfer of a plot of land from one party to another, where the transfer of ownership rights to the land is desired by both parties through buying and selling. In Article 19 of Government Regulation Number 10 of 1961 stipulates that the sale and purchase of land must be proven by a deed made by and before the Land Deed Making Officer (PPAT), meaning that at that time the rights have also passed from the seller to the buyer. As for the requirements in the transfer of land ownership rights, namely: application form that has been filled out and signed by the applicant or his proxy on stamp duty, photocopy of the applicant's identity (KTP, KK), Deed of sale and purchase (AJB), etc. The data collection method used in this research is the method of interview, observation, and documentation. In this study, the data analysis method used is qualitative analysis, because it describes the implementation of the registration of the transfer of ownership of land in the sale and purchase agreement. The purpose of this study is to describe the procedure for registering the transfer of ownership of land by buying and selling at the National Land Agency Office of South Nias Regency, to describe what obstacles are faced at the South Nias Regency BPN Office and to describe solutions in overcoming the various obstacles that arise. occur. The results of the study indicate that, every transfer of ownership rights to land with a sale and purchase agreement, after the transfer of rights by the PPAT as evidenced by the deed of sale and purchase, then the PPAT concerned within 7 working days from the signing of the deed, must register the transfer of ownership rights to the land at The Land Office, especially at the BPN Office of South Nias Regency, brings the required applicant files. In providing services through the counter system